Road Geometry Horizontal Alignment Planning Using Manual Design Method (Case Study Highway Kejayaan District – Pasrepan District, Pasuruan Regency, East Java STA 2+566 to STA 5+164) - Joshua Joshua; Andri Irfan Rifa'i (Fakultas Teknik Sipil dan Perencanaan, 2023)
Pasuruan is a district in East Java Province, Indonesia. The capital city is Bangil District. Adequate transportation is one of the needs of the community. Along with the growing economic growth will also increase the volume of transportation in the region. Road transport safety is a global issue. Due to the large number of traffic accidents that occur, good road planning is needed, the geometric shape must be determined in such a way that the road in question can provide safety for road users in traffic. aims to carry out geometric planning of roads, especially horizontal alignment case studies of highways of Glory District – Pasrepan District STA 2+566 to.d. STA 5+164 Pasuruan Regency, East Java. In this study, it was concluded that the road is a primary collector road with a design speed of 80 km/hour, and a maximum slope (e) of 8%. With the road classification of the first and second Full Circle bends, as well as the third corner of the Spiral Circle Spiral. From the calculations, the horizontal arch length (Lc) at the first bend is 170.4095 m, at the second bend is 342.155 m, and at the third bend is 50.637 m.